Based on Acceptable Parameters of Irrigation Technique Elements in Irrigation of Bukhara-6 Variety of Cotton in Conditions of Water Shortage (Texas Journal of Agriculture and Biological Sciences, 2022)
Groundwater is located deep (3 meters), gray and clay soils with medium mechanical composition, gravelly and sandy soils (II hydromodule region) are scattered, with low moisture retention capacity. za is watered 9 times in the 3-5-1 system. In this case, the day between irrigations is 15-12-15 days. Gray and clay soils (III hydromodule region) are irrigated 7 times in the 2-4-1 system, and the interval between irrigations is 16-14-25 days. In the conditions of sand and loamy soils (IV hydromodule region), cotton is watered 9 times in the 3-5-1 system, with 12-13-25 days between waterings, heavy gray, gray, mechanical in the conditions of different or dense layered soils (VI hydromodule region), it is irrigated 6 times in the 1-41 system, 16-15-25 days between irrigations, 2-5 in sandy and loamy soils where seepage water is located at 1-2 meters - Watered 8 times in 1 system, 15-12-20 days between waterings, seepage water 1-2 meters, light, gray homogenous medium and heavy soils 1-3-0 and 1- Watered 4-5 times in 3-1 systems, 17-15-25 days between waterings, in heavy, gray and clay soils with high water permeability, seepage water is located at 1-2 meters 1-3- It is watered 5 times in 1 system, and the intervals between waterings are 19-16-25 days